PENGEMBANGAN ALUR TUJUAN PEMBELAJARAN (ATP) MATA PELAJARAN ILMU PENGETAHUAN ALAM (IPA) KELAS VII SMP - Tri Riswakhyuningsih (Bapelitbang Kabupaten Batang, 2022)
The purpose of the study was to find out the results of the Flow of Learning Objectives validation of science subjects for class VII Junior High School. which was developed and to know the results of a limited trial of using Flow of Learning Objectives for science subjects for class VII Junior High School which was developed as a reference in designing teaching modules. The research was conducted using the Research and Development (R&D) method. The subject of this research is the formulation of Flow of Learning Objectives for science subjects for class VII Junior High School. The object of research is the components of Flow of Learning Objectives. The data sources in this study are the results of Flow of Learning Objectives validation and the results of trials using Flow of Learning Objectives. Non-test technique used to collect data. Data collection instruments used Flow of Learning Objectives review sheets and study modules. Flow of Learning Objectives validation expert validation, logistic validation, and internal validation. Data analysis was carried out descriptively based on the results of the assessment with the help of a rubric. The validation results show that the Flow of Learning Objectives Criteria developed are good so that they can be used in learning. The trial results show that the developed Flow of Learning Objectives is easy to use. Keywords: Flow of Learning Objectives, Natural Sciences, Junior High School.